External beam radiotherapy with or without concurrent chemotherapy in advanced or recurrent non‐anaplastic non‐medullary thyroid cancer. Issue 4 (24th June 2014) - Romesser, Paul B.; Sherman, Eric J.; Shaha, Ashok R.; Lian, Ming; Wong, Richard J.; Sabra, Mona; Rao, Shyam S.; Fagin, James A.; Tuttle, R. Michael; Lee, Nancy Y.
<x xml:space="preserve">Abstract</x> Background and Objectives To review clinical outcomes and toxicities in locally advanced differentiated thyroid cancer patients treated with external beam radiotherapy (EBRT) with or without concurrent chemotherapy (CCRT). Methods Between 1990 and 2012, 66 patients with gross residual/unresectable non‐anaplastic non‐medullary thyroid cancer were treated with EBRT. Results The median overall survival was 42.0 months. The overall locoregional progression‐free survival (LPFS) at 3 years was 77.3%. CCRT resulted in a non‐significant improvement in LPFS (90.0% vs. 73.0%, P = 0.347). Poorly differentiated histology had significantly improved LPFS (89.4% vs. 66.1%, P = 0.020), despite a significantly worse distant metastasis‐free survival (43.9% vs. 82.5%, P = 0.023). Acute treatment‐related toxicity included dermatitis, mucositis, and dysphagia with grade three rates of 12.1%, 19.7%, and 16.7%, respectively. The incidence of late toxicity was low. CCRT was only associated with a significant greater rate of acute grade 3 hoarseness (10.0% vs. 0.0%, P = 0.033), but with no difference in the rate of grade 2 late toxicity. Conclusions EBRT is a safe and effective treatment modality with 90% LPFS at 3 years in patients with gross residual or unresectable non‐anaplastic, non‐medullary thyroid carcinoma treated with CCRT. Further incorporation of EBRT with concurrent chemotherapy may result in improved disease control. J. Surg. Oncol. 2014; 110:375–382. © 2014 Wiley Periodicals, Inc.